Menguak Perilaku Masyarakat dalam Pemanfaatan Lahan Teba di Desa Sulangai, Kecamatan Petang, Kabupaten Badung - Mahadewi, Ni Made Anggita Sastri (Jurnal Ilmiah Widya Sosiopolitika; Vol 6 No 2 (2024): ISU-ISU PEMBANGUNAN, 2025)
Teba is the backyard behind the house that used for the growth of plants and animal life, it’s not only for ecologically, but also socially and religiously. But, the behavior of throwing garbage into teba is still entrenched in the community. To overcome this problem, the Balinese have their own way of managing the traditional household waste that they produce, including as fodder for pigs and as fertilizer for crops, or by burning it on teba which is usually used as a place to manage garbage (household waste that is easy to recycle), a place for raising and cultivating orchards and various types of wood trees for building materials. The theory of Ecocentrism (Deep Ecology) sees that basically Balinese people in general have local wisdom that is very useful to be implemented in coexistence with nature. However, because of changes in lifestyle as it is today, people are starting to put these things aside and prioritize profit alone. In addition, the concept of Tri Hita Karana , it called a harmony relationship with nature/environment. Wana Kertih and Palemahan should really be used as a way of life, so that teba as a form of the environment that is closest to people's daily lives can be kept clean and moreover can be used better, rather than being a place to throw garbage.